Pelatihan Analisis Kinerja Konten Media Sosial Shofi Cookies dengan Data Analytics - Syandra Sari; Dedy Sugiarto; Ratna Shofiati; Anung B Ariwibowo; Shabrina Teruri; Muhamad Ichsan Gunawan; Faiz Kumara; M Arya Octavianus (Pusat Riset dan Inovasi Nasional, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy but still face challenges in utilizing digital technology for marketing. Shofi Cookies, as the partner of this program, has been using TikTok and a website, yet their utilization remains suboptimal. This community service activity aimed to enhance the partner’s digital capacity through social media analysis, website audits, and digital branding training. The methods included evaluating the TikTok account, auditing the website’s Search Engine Optimization (SEO), and providing training on the use of WordPress Content Management System (CMS) along with branding strategies. The results showed that the TikTok account was still personal, limiting analytic data, while the website audit produced a C- SEO score with issues in mobile access speed. The training, attended by the owner and operator, received positive responses with high satisfaction, although participants’ understanding still needs improvement. The implication of this activity highlights the importance of follow-up actions such as switching to a TikTok business account, increasing content upload consistency, and optimizing website SEO. With these efforts, Shofi Cookies is expected to strengthen competitiveness, expand market reach, and increase sales in the digital era.